Complementary Feeding with Genesis Stunting in Children: A Systematic Review - Niswa Salamung; Nessy Anggun Primasari; Melinda Restu Pertiwi; Siti Riskika (Universitas Bondowoso, 2020)
Introduction: Stunting is a problem of chronic malnutrition caused by insufficient nutrition in a long time due to feeding that is not in accordance with nutritional needs. One of the problems in feeding infants is the cessation of breastfeeding breastmilk and insufficient complementary feeding. The purpose study literature review is to identify thecomplementary feeding with the incidence of stunting in children. Method: The authors conducted a relevant literature review in various data using the keywords “complementary feeding, stunting, child”. Data based on SCOPUS, Science Direct, Proquest, Pubmed and Scholar.The criteria consisted of full text published in criteria were five years limit journal (2013-2018) use article using English. Result:The Results as much as 2.090 articles found, and selected 15 article that suitable with criteria. On the process of the analysis of the articles showed that timely complementary foods, frequency of food and drinks, diversity of foods and drinks associated with the incidence of stunting. in the study of the dietary patterns of all children using the 24-hour recall food questionnaire. Interventions focusing on optimal nutrition during the complementary feeding stage, exclusive breastfeeding, and the use of deworming tablets. Good complementary feeding potential to improve children's nutritional status and can prevent stunting in children after 0-59 month. Conclusion: stunting is influenced by the accuracy of complementary feeding, exclusive breastfeeding for 6 months, frequency of eating and drinking, diversity of iron and vitamin A-rich foods and regular administration of worm medicine.